A Comparison of the Representation of Women in Editor Positions at Major Medical Journals in 2021 vs 2011. (6th September 2022) - Starchl, Christina; Shah, Vianca; Zollner-Schwetz, Ines; Knezevic, Jovana; Geiger, Simon; Amrein, Karin
Abstract : Purpose: There continues to be a disparity in the representation of women across medicine, including in editor positions at major medical journals. The authors repeated a study they had conducted in 2011 to compare the representation of women in editor-in-chief and editorial board member positions in 2011 and 2021. Method: The authors included in their analysis the 60 journals from their original 2011 study and the top 5 ranked journals by Journal Impact Factor in each of 12 disciplines in 2021. This led to the inclusion of 86 journals. The authors collected the names and genders of the editors-in-chief and editorial board members at these journals, using information provided by the journals and a Google search for the photos and/or pronouns of the remaining editors. They compared results across years (2021 vs 2011), editor positions, disciplines, Journal Impact Factors, and ranks. Results: Twenty-two of the 90 editors-in-chief (24.4%) were women in 2021 compared with 10 of 63 (15.9%) in 2011, an increase of 8.5%. Of the 6, 285 editorial board members, 1, 756 were women (27.9%) in 2021 compared with 719 of 4, 112 (17.5%) in 2011, an increase of 10.4%. Journals with women editors-in-chief gained 3.5 ranks and 9.1 points in Journal Impact Factor on average over this 10-year period, compared with no gain in rank and an increase of 4.7 points in Journal Impact Factor for journals with men editors-in-chief; both are statistically significant differences ( P = .045 and P = .016, respectively). Conclusions: In almost all evaluated disciplines and editor positions, there was an increase in the percentage of women at top-ranked medical journals over a 10-year period. Despite this increase, improvements are still needed to accelerate the currently slow rate of change in these positions to enhance diversity, equity, and inclusion for women in medicine.